2022
DOI: 10.1111/codi.16096
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, prospective cohort study of handsewn versus stapled intracorporeal anastomosis for robotic hemicolectomy

Abstract: There has been a longstanding debate regarding the optimal anastomotic technique in minimally invasive right hemicolectomy, namely intracorporeal anastomosis (ICA) or extracorporeal anastomosis (ECA) and handsewn or stapled anastomosis. The current evidence base suggests that ICA is associated with faster gastrointestinal recovery, a shorter length of stay and reduced opiate consumption [1]. However, despite these demonstrable benefits, ECA is employed more widely due to its ease of formation. Furthermore, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Recent studies have reported uniformly low rates of anastomotic leakage. The overall reported rates of anastomotic leak following robotic right colectomy are low, ranging between 0.9% and 3.8% [24][25][26]. Regarding SSI, theoretically, the intraperitoneal incision into the bowel lumen in IA may cause fecal spillage, which can lead to SSI.…”
Section: Postoperative Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported uniformly low rates of anastomotic leakage. The overall reported rates of anastomotic leak following robotic right colectomy are low, ranging between 0.9% and 3.8% [24][25][26]. Regarding SSI, theoretically, the intraperitoneal incision into the bowel lumen in IA may cause fecal spillage, which can lead to SSI.…”
Section: Postoperative Outcomesmentioning
confidence: 99%
“…Recent studies have reported uniformly low rates of anastomotic leakage. The overall reported rates of anastomotic leak following robotic right colectomy are low, ranging between 0.9% and 3.8% [ 24 - 26 ].…”
Section: Postoperative Outcomesmentioning
confidence: 99%